Super-Nernstian pH Sensor Based on Anomalous Charge Transfer Doping of Defect-Engineered Graphene - Jung, Su Ho; Seo, Young Min; Gu, Taejun; Jang, Wonseok; Kang, Seog Gyun; Hyeon, Yuhwan; Hyun, Sang Hwa; Lee, Jae Hyun; Whang, Dongmok (Nano Letters, 2021)
The conventional pH sensor based on the graphene ion-sensitive field-effect transistor (Gr-ISFET), which operates with an electrostatic gating at the solution-graphene interface, cannot have a pH sensitivity above the Nernst limit (∼59 mV/pH). However, for accurate detection of the pH levels of an aqueous solution, an ultrasensitive pH sensor that can exceed the theoretical limit is required. In this study, a novel Gr-ISFET-based pH sensor is fabricated using proton-permeable defect-engineered graphene. The nanocrystalline graphene (nc-Gr) with numerous grain boundaries allows protons to penetrate the graphene layer and interact with the underlying pH-dependent charge-transfer dopant layer. We analyze the pH sensitivity of nc-Gr ISFETs by adjusting the grain boundary density of graphene and the functional group (OH-, NH2-, CH3-) on the SiO2 surface, confirming an unusual negative shift of the charge-neutral point (CNP) as the pH of the solution increases and a super-Nernstian pH response (approximately -140 mV/pH) under optimized conditions.
Keywords: Charge transfer doping; Grain boundary densities; Graphene layers; Nanocrystallines; Negative shift; Optimized conditions; Theoretical limits; Ultra sensitives; charge transfer; defect engineering; graphene; Nernst limit; pH sensor